Regulation of Social Recognition Memory in the Hippocampal Circuits - Wang, Xinnian; Zhan, Yang (Frontiers in Neural Circuits, 2022)
Social recognition memory reflects the ability of the social animals to recognize and remember familiar individuals of the same species. The unique ability for mammals to recognize conspecifics is essential and beneficial when animals conduct daily social activities. This brief review summarizes a brain network underlying social recognition memory and explores the possible relationships between social isolation and social recognition memory. Finally, we introduce some possible related molecular mechanisms underlying social recognition memory. These findings help us explore potential targeting brain areas or circuits of social communication disorder.